2009
DOI: 10.1001/archgenpsychiatry.2009.109
|View full text |Cite
|
Sign up to set email alerts
|

Association of Time Since Deployment, Combat Intensity, and Posttraumatic Stress Symptoms With Neuropsychological Outcomes Following Iraq War Deployment

Abstract: In this study of army soldiers deployed to the Iraq war, only PTSD symptoms (among soldiers back from deployment for 1 year) were associated with a neuropsychological deficit (reduced attention). Greater combat intensity was associated with enhanced reaction time, irrespective of time since return.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 61 publications
(65 reference statements)
3
52
0
Order By: Relevance
“…In another longitudinal sample of predominantly male, war-deployed soldiers, higher PTSD symptom levels were associated with worse attention one year after returning from deployment, over and above pre-deployment attention. [19] Furthermore, initial research in predominantly male samples of treatment-seeking older veterans has found that PTSD is associated with an approximately two-fold increased risk of incident dementia. [2022] Notably, associations of PTSD with cognitive function have been largely independent of depression.…”
Section: Introductionmentioning
confidence: 99%
“…In another longitudinal sample of predominantly male, war-deployed soldiers, higher PTSD symptom levels were associated with worse attention one year after returning from deployment, over and above pre-deployment attention. [19] Furthermore, initial research in predominantly male samples of treatment-seeking older veterans has found that PTSD is associated with an approximately two-fold increased risk of incident dementia. [2022] Notably, associations of PTSD with cognitive function have been largely independent of depression.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD co-occurs with SUD among roughly 40 % of civilians and veterans [2, 5, 6]. Individuals with co-occurring SUD and PTSD incur heightened risk for other psychiatric problems (e.g., depression, anxiety), suicidality, neuropsychological impairment, increased morbidity and mortality, unemployment, and social impairment [2, 5, 7, 8]. This complex comorbidity also places a tremendous economic burden on the healthcare system, as it results in poorer treatment outcomes, longer duration of substance use, and more treatment episodes [912].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include children with attention-deficit hyperactivity disorder (Bolfer et al, 2010; Chamberlain et al, 2011; Gualtieri & Johnson, 2006; Polderman, van Dongen, & Boomsma, 2011) or depression (Brooks, Iverson, Sherman, & Roberge, 2010); adults with psychiatric illnesses, such as depression or bipolar disorder (Iverson, Brooks, Langenecker, & Young, 2011; Sweeney, Kmiec, & Kupfer, 2000); and adolescents and young adults who sustain sport-related concussions (Bleiberg, Garmoe, Halpern, Reeves, & Nadler, 1997; Bleiberg et al, 2004; Broglio, Ferrara, Macciocchi, Baumbartner, & Elliott, 2007; Cernich, Reeves, Sun, & Bleiberg, 2007; Collie, Makdissi, Maruff, Bennell, & McCrory, 2006; Collins, Lovell, Iverson, Ide, & Maroon, 2006; Gualtieri & Johnson, 2008; Iverson, Brooks, Collins, & Lovell, 2006; Iverson, Brooks, Lovell, & Collins, 2006; Peterson, Stull, Collins, & Wang, 2009; Van Kampen, Lovell, Pardini, Collins, & Fu, 2006). CNADs have also been applied to adult epilepsy (Moore, McAuley, Long, & Bornstein, 2002), cardiovascular surgery (Raymond, Hinton-Bayre, Radel, Ray, & Marsh, 2006), neurocognitive problems encountered by active duty military service members and veterans (Anger et al, 1999; Marx et al, 2009; McLay, Spira, & Reeves, 2010; Retzlaff, Callister, & King, 1999; Vasterling et al, 2006), and mild cognitive impairment in older adults (Doniger et al, 2006; Dwolatzky et al, 2004; Gualtieri & Johnson, 2005; Tornatore, Hill, Laboff, & McGann, 2005; Wild, Howieson, Webbe, Seelye, & Kaye, 2008) or dementia (Doniger et al, 2005; Dorion et al, 2002; Wouters, de Koning et al, 2009; Wouters, Zwinderman, van Gool, Schmand, & Lindeboom, 2009). Computerized tests, sometimes administered as part of a predominantly examiner-administered battery, are also used to identify poor effort within the context of a comprehensive neuropsychological evaluation (Green, Rohling, Lees-Haley, & Allen, 2001; Slick et al, 2003).…”
Section: Introductionmentioning
confidence: 99%